Bioactivity of Marine Organisms: Part XI- Screening of some Marine Flora from the Indian Coasts - Lakshmi, V; Goel, AK; Srivastava, MN; Raghubir, R (Bangladesh Journal of Scientific and Industrial Research, 2010)
With a view to explore of finding the new molecules with therepeutic efficacy for human use, the alcoholic extracts of 33 indentified species of marine flora, collected from Indian coasts, were prepared and screened for a wide range of biological activities. Of these, 1 extract showed antifilarial activity, 1 showed antiamoebic effect and the 1 showed antitrichomonas activity. Key words: Marine flora; Ethanol extracts; Broad biological screening; 3 active extracts. DOI: 10.3329/bjsir.v45i3.6537 Bangladesh J. Sci. Ind. Res. 45(3), 271-276, 2010